HUBUNGAN DISABILITAS PADA PASIEN PASCA STROKE DENGAN TINGKAT DEPRESI PADA LANSIA DI RUMAH SAKIT OTAK DR. DRS. M. HATTA BUKITTINGGI TAHUN 2021 - siska Damaiyanti; Dewi Kurniawati (STIKes Al-Insyirah Pekanbaru, 2022)
Disability in post-stroke clients in the form of decreased function of the extremities, such as the presence of hemiparesis in the extremities. The disability experienced by stroke patients triggers the emergence of stress to depression due to the patient's inability to meet internal and external demands. The purpose of this study was to determine the relationship between disability in post-stroke patients and the level of depression in the elderly at the Brain Hospital DR. Drs. M. Hatta Bukittinggi in 2021. This type of research is descriptive correlation with a cross sectional approach. The population in this study were elderly post-stroke patients who were outpatient with a sample of 81 people using cluster random sampling technique. The instrument of this study used the Barthel Index and GDS questionnaires. The test used is Spearman rank. The results showed that almost half of the elderly post-stroke patients had disabilities in the independent category (44.4%), some of the elderly post-stroke experienced mild and normal (39.5%), obtained p-value = 0.000 < (0.05) and value of r = 0.639. It can be concluded that there is a relationship between disability in post-stroke patients and the level of depression in the elderly at the Brain Hospital DR. Drs. M. Hatta Bukittinggi in 2021, which shows a strong and statistically significant relationship between disability in post-stroke patients and the level of depression in the elderly. Suggestions to nurses in hospitals, can be used as input for developing nursing knowledge, so nurses can improve the quality of services in providing nursing care, especially for elderly patients with post-stroke disabilities.